Primary Care and Community-Based Partnerships to Enhance HPV Vaccine Delivery - Patricia A. Carney PhD, MS; Marie B. Engstrom MPH; Chrystal Barnes BS; NithyaPriya Ramalingam PhD; Caitlin Dickinson MPH; Cort Cox; Laura K. Ferrara; Paul M. Darden MD; Lyle J. Fagnan MD; Miguel Marino PhD; Brigit A. Hatch MD, MPH (SAGE Publishing, 2024)
Introduction/Objectives: With growing vaccination misinformation and mistrust, strategies to improve vaccination communication across community-based settings are needed. Methods: The Rural Adolescent Vaccine Enterprise (RAVE), a 5-year (2018-2022) stepped-wedge cluster randomized study, tested a clinic-based practice facilitation intervention designed to improve HPV vaccination. An exploratory aim sought to explore the use of partnerships between primary care clinics and a community partner of their choosing, to implement a social marketing campaign related to HPV immunization. We assessed perceptions about the value and success of the partnership, and barriers and facilitators to its implementation using a 29-item community partner survey, key informant interviews, and field notes from practice facilitators. Results: Of the initial 45 clinics participating in RAVE, 9 were unable to either start or complete the study, and 36 participants (80.0%) were actively engaged. Of these, 16/36 clinics (44.4%) reported establishing successful partnerships, 10 reported attempting to develop partnerships (27.8%), and another 10 reported not developing a partnership (27.8%), which were often caused by the COVID-19 pandemic. The most common partnership was with public health departments at 27.3%. Other partnerships involved libraries, school districts, and local businesses. More than half (63.7%) reported that creating messages regarding getting HPV vaccination was moderately to very challenging. Just under half reported (45.5%) that messaging was hard because of a lack of understanding about the seriousness of diseases caused by HPV, parents being against vaccines because of safety concerns, and religious values that result in a lack of openness to HPV vaccines. Community partners' health priorities changed as a result of RAVE, with 80% prioritizing childhood immunizations as a result of the RAVE partnership. Conclusions: Community groups want to partner with primary care organizations to serve their patients and populations. More research is needed on how best to bring these groups together.